Targeting acetylcholine receptor M3 prevents the progression of airway hyperreactivity in a mouse model of childhood asthma. Issue 10 (19th September 2017) - Patel, Kruti R.; Bai, Yan; Trieu, Kenneth G.; Barrios, Juliana; Ai, Xingbin
ABSTRACT: Asthma often progresses into adulthood from early‐life episodes of adverse environmental exposures. However, how the injury to developing lungs contributes to the pathophysiology of persistent asthma remains poorly understood. In this study, we identified an age‐related mechanism along the cholinergic nerve–airway smooth muscle (ASM) axis that underlies prolonged airway hyperreactivity (AHR) in mice. We showed that ASM continued to mature until ~3 wk after birth. Coinciding with postnatal ASM maturation, there was a critical time window for the development of ASM hypercontractility after cholinergic stimulation. We found that allergen exposure in neonatal mice, but not in adult mice, elevated the level and activity of cholinergic nerves (termed neuroplasticity). We demonstrated that cholinergic neuroplasticity is necessary for the induction of persistent AHR after neonatal exposure during rescue assays in mice deficient in neuroplasticity. In addition, early intervention with cholinergic receptor muscarinic (ChRM)‐3 blocker reversed the progression of AHR in the neonatal exposure model, whereas β2‐adrenoceptor agonists had no such effect. Together, our findings demonstrate a functional relationship between cholinergic neuroplasticity and ASM contractile phenotypes that operates uniquely in early life to induce persistent AHR after allergen exposure. Targeting ChRM3 may have disease‐modifying benefits in childhood asthma.—Patel, K. R., Bai, Y., Trieu, K. G., Barrios, J., Ai, X. Targeting acetylcholine receptor M3 prevents the progression of airway hyperreactivity in a mouse model of childhood asthma. FASEB J. 31, 4335–4346 (2017). www.fasebj.org